General mental health and new media literacy among Malaysian adult urbanites - Emeralda, Dee; Che Hasan, Abdul Hadi; Ho, Yi Ming; Prihadi, Kususanto Ditto (Intelektual Pustaka Media Utama, 2025)
This study investigates the multifaceted interplay of risk and protective factors influencing general mental health (GMH), focusing on the impact of external validation seeking through online interactions and the protective role of perceived social support (PSS) against GMH problems, mediated by unconditional self-acceptance (USA) and PSS with new media literacy (NML) is introduced as a moderator variable, affecting the interplay between PSS, USA, and interpersonal mattering (IPM) in predicting GMH. A moderated serial mediation model was proposed and tested with 380 purposively recruited adult urbanites from Malaysia. The results reveal that individuals with high NML perceive greater social support, leading to higher self-acceptance and mattering, enhanced GMH protection. This study highlights the critical role of NML in the digital age’s impact on GMH.